Understanding the role of C16orf72 in the DNA replication stress response - Kosmin, J (2022)
The human genome continually undergoes DNA damage that is endogenous and exogenous in origin. To protect the genome from this DNA damage, cells have evolved a plethora of signalling pathways, known as the DNA damage response (DDR). The poly(ADP-ribose) polymerase (PARP) enzyme family can regulate a variety of DDR pathways by modifying substrates with ADP-ribose, a type of chemical post-translational modification. However, our understanding of these pathways, and the factors involved in them, remains in their infancy. Chemical inhibitors of PARPs (PARPi) have emerged as key therapeutic tools to combat human diseases, thereby underlining the importance of understanding the pathways controlled by this enzyme family.